2018
DOI: 10.1021/acs.chemmater.8b00628
|View full text |Cite
|
Sign up to set email alerts
|

Pore-Engineered Silica Nanoreactors for Chemical Interaction-Guided Confined Synthesis of Porous Platinum Nanodendrites

Abstract: Designing and synthesizing noble metal nanostructures with tunable porosity and nanoscopic intricacies is crucial for highly augmented surface properties and as gateway to the wide range of applications. Here, we develop a pore-engineered nanoreactor (PENR)-based approach toward the synthesis of porous platinum nanodendrites (PtNDs) of “yolk-in-shell” and “shell-in-shell” morphologies and with tunable nanoscale porosity. In our strategy, first, various silica-based PENRs with variable porosity and each contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…The as‐synthesized ZIF‐67@HCSs exhibited a unique core–shell structure composed of single microporous carbon shell and several nanoscale ZIF‐67 cores. Due to the nanoconfined environment inside HCSs, these nanoreactors outperformed the conventional solution‐based synthesis . The results showed that: (1) the huge inner space of HCSs could be fully utilized without volume expansion, thus enhancing the tap density; (2) space‐confined synthesis could control the size and morphology of ZIF‐67 nanoparticles; (3) high chemical and thermal stability of ZIF‐67 nanoparticles protected by hydrophobic carbon shell can avoid the moisture effects for real postcombustion gas separation, and therefore enhance the long‐term stability.…”
Section: Introductionmentioning
confidence: 99%
“…The as‐synthesized ZIF‐67@HCSs exhibited a unique core–shell structure composed of single microporous carbon shell and several nanoscale ZIF‐67 cores. Due to the nanoconfined environment inside HCSs, these nanoreactors outperformed the conventional solution‐based synthesis . The results showed that: (1) the huge inner space of HCSs could be fully utilized without volume expansion, thus enhancing the tap density; (2) space‐confined synthesis could control the size and morphology of ZIF‐67 nanoparticles; (3) high chemical and thermal stability of ZIF‐67 nanoparticles protected by hydrophobic carbon shell can avoid the moisture effects for real postcombustion gas separation, and therefore enhance the long‐term stability.…”
Section: Introductionmentioning
confidence: 99%
“…We started the synthesis of NCat from hollow and porous aminated silica nanoshells ( h ‐SiO 2 , 75±3 nm diameter, ca. 10 nm thickness) modified with Au‐seeds ( AuNC@ h ‐SiO 2 ) and coated with a thin conformal film (ca. 3 nm) of TA‐Fe coordination polymer using a modified reported chemistry (Figure S1) .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in the transmission electron microscopy (TEM) image of Au‐4‐NCat (Figure a), the outer Au‐layer grew slightly thicker (14±1 nm) than the inner Au‐layer (11±1 nm), forming a structure collectively evolving as a hollow concentric metallic bilayer configuration, where each Au‐layer is composed of arrays of closely spaced AuNP‐units; and the interlayer space comprises massive number of few‐nm cavities confined by AuNPs, which remain accessible through the narrow interparticle channels among the non‐coalesced AuNP‐units. In the plausible Au‐growth mechanism, the TA‐Fe nanofilm deassembles in the presence of HAuCl 4 , due to the pH‐dependent reversible Fe III ‐TA co‐ordination chemistry and generates TA‐oligomers having plenty of free catecholic moieties on the surface of AuNC@ h ‐SiO 2 ; followed by the directed approach of Au 3+ towards the outer and inner Au‐seeds permeating through the microporous aminosilica‐layer (Figure a) . Replacing hydroquinone with other reducing agents did not result the desired Au‐bilayer structure (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…The methanol oxidation reaction (MOR) is crucial to DMFCs, and developing high‐efficiency, stabilized, and economical electrocatalysts for the MOR is important for the broad deployment and widespread commercialization of DMFCs . It is known that platinum nanomaterials are significant catalysts, owing to their outstanding performance in catalyzing the MOR . However, the high cost, low utilization, and CO poisoning of Pt materials hinder their development .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] It is known that platinum nanomaterials are significant catalysts, owing to their outstandingperformance in catalyzing the MOR. [7][8][9][10][11][12][13][14] However,t he high cost, low utilization, and CO poisoning of Pt materials hinder their development. [15][16][17][18][19] Great efforts have been devoted to developing promisingP t-basedc atalysts, such as reducing catalyst expense, combining Pt with transition metals,a nd modifying the electronic structure.…”
Section: Introductionmentioning
confidence: 99%